Private security, public order the outsourcing of public services and its limits - Chesterman, Simon; Fisher, Angelina (Oxford : Oxford University Press, 2009)
Public functions are increasingly being outsourced to the private sector. This includes activities that impact on human rights and security. Drawing on insights from various disciplines, this book looks at the costs and benefits of privatization and at whether there are limits to this trend.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Private security services -- Law and legislation; Police, Private; Private military companies; Security, International; Mercenary troops; National security